PERILAKU MENYUSUI PADA IBU DENGAN TINGKAT SOSIAL EKONOMI RENDAH DI KECAMATAN SIDOHARJO, SRAGEN - Intan Pratama; Martha Irene Kartasurya; Yudhy Dharmawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Breastfeeding behavior to infants is influenced by knowledge, attitude, and practice. The PuskesmasSidoharjo has an exclusive coverage of low ASI (38.3%) when compared to the target of the strategic plan (80%). The objective of the study was to describe breastfeeding behavior in low socioeconomic mother in Sidoharjo sub-district, Sragen. The research was qualitative research with descriptive method. Key informants are 4 mothers who have 7 month old babies each from low socioeconomic group, working and not working and give exclusive and non exclusive breastfeeding. Triangulation informants are family members who live with mothers and village midwives. The results showed that women with low socioeconomic status, working or not working, still provide exclusive breastfeeding because they are aware of health status, smooth milk flow, and economical reasons. Mother who are working or does not working but does not give exclusive breastfeeding because it has a nipple problem that is not prominent. It is concluded that good knowledge and attitudes about exclusive breastfeeding are not always applied in exclusive breastfeeding practices, because there are problems of organic abnormalities and practical reasons for working mothers.